Beyond Biology : Rethinking Parenthood in the Catholic Tradition - Kohlhaas, Jacob M. (Book collections on Project MUSE., 2020)
"This book, to be published in the Moral Traditions series, aims to overcome currently accepted Catholic frameworks for conceptualizing parenthood and to provide new foundations for a more robust theological reflection on parenthood. It begins by arguing that contemporary official Catholic accounts of parenthood are highly influenced by matters of sexual ethics and ideologies of gender that obscure consideration of parenthood in its own right. In addition, even as revisionist scholars have challenged specific Church teachings, they too have largely accepted the grounds for debate asserted within magisterial documents. While sexual and reproductive ethics are important, the unwitting consensus that theological consideration of parenthood ought to hinge on these matters has diverted attention from the actual practices of parenthood viewed in their entirety throughout the life course and within the complex negotiations of kinship and caregiving. In response, this project initiates the task of constructing a broader and richer theological anthropological account of parenthood through a historical, critically appreciative, and interdisciplinary theological method. By marshaling the diversity of the Christian tradition and drawing attention to the interpretive decisions that have framed current modes of discourse, as well as exploring contemporary research in the social sciences and humanities, it frames a new theological conversation on parenthood as parenthood. In this task, conceptions of parenthood are guided by the nature and meaning of Christian kinship as well as concern for the actual caregiving capacities of adults and the needs of children. Ultimately, this call for a renewed and expanded conversation utilizes the interpretive options within the Catholic tradition to create room for meaningful, intellectually convincing, and theologically rich responses to challenges facing Christian parents and families today"--